A study on Relationship between firm size and profitability: Selected Private sector Banks in India - Rengasamy, Dhanuskodi (International Journal of Trend in Scientific Research and Development, 2019)
The study is to identify the relationship between firm size and profitability of selected private sector banks in India. This study is classified as quantitative research followed with a descriptive research design. The Reserve Bank of India’s publication of annual trend and progress of banking in India in June 2018, indicates that the total number of private sector banks in India is 21. The study selected the first five banks based on the hierarchy of the value of its total assets. The study is based on secondary data and it has been collected from the annual reports of the respective banks. The period of study is five years from 2015 to 2019. Firm size such as bank size is measured through the natural log of the book value of deposits, assets, and advances (independent variables) and the profitability is measured through the natural log of the book value of the net profit of the bank (dependent variable). The data analysis includes descriptive statistics, correlation matrix, and linear regression. On the basis of the analysis, the study found that there is a significant relationship between independent variables and the dependent variable. Further, there is a positive correlation and statistically significant between these variables. Keywords : Bank size, deposits, assets, advances, net profit